Knowledge, attitude and confidence level of resuscitation among house officer in Hospital Universiti Sains Malaysia - Ping, Lee Wui (2020)
Background: House officers are often the first responder involved in hospital management of emergency situations. We noticed some of them are hesitant in providing resuscitation. Therefore, we aim to evaluate knowledge in general resuscitation, attitude and confidence level in general resuscitation in emergency situations and identify its associated factors. Materials and method: A cross-sectional study was conduct among house officers from 27 May 2018 to 31 December 2018 in Hospital Universiti Sains Malaysia (HUSM), using a validated questionnaire. One-hundred house officers consented and completed the questionnaire were included. Fourteen incomplete questionnaires were excluded. Descriptive analysis, simple and multiple logistic regression analysis were performed via SPSS version24.0. P-value < 0.05 were considered to be statistically significant. Result: Only 35% house officers showed adequate knowledge, 24% were confident in performing resuscitation and 97% had positive attitude toward learning resuscitation. House officer received trauma life support training during housemanship (adjusted OR:10.9,95%CI : 1.197 to 99.240, p-value: 0.034)and had ≥10 times clinical exposure to CPR( adjusted OR: 3.933, CI95% : 1.249 to 12.385, p-value : 0.019) more likely to have adequate knowledge compared to those had not. Conclusion: Overall, house officers have lack of knowledge and confidence in resuscitation. However, most of them had positive attitude toward learning resuscitation. Frequent assessment, revision, refreshment of updated guideline and resuscitation technique at regular interval is necessary to improve their knowledge and confident level in resuscitation.